2009
DOI: 10.1586/era.09.113
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab in metastatic or recurrent head and neck cancer: the EXTREME trial

Abstract: Expression of EGF receptor (EGFR) is frequently elevated in squamous cell carcinoma of the head and neck (SCCHN). Cetuximab is an anti-EGFR monoclonal antibody that has been shown to improve overall survival in patients with locally advanced SCCHN when combined with radiotherapy. Data from Phase II trials suggest an interesting activity of cetuximab in patients with recurrent or metastatic SCCHN who are refractory to cisplatin. The Erbitux in First-Line Treatment of Recurrent or Metastatic Head and Neck Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 53 publications
2
60
0
1
Order By: Relevance
“…A recently published phase III EXTREME study showed that adding Cetuximab (human chimeric monoclonal antibody against EGFR) to platinum and 5-FU significantly prolonged the median OS from 7.4 months to 10.1 months in recurrent and/or metastatic SCCHN. 24 Quality of life (QOL) measurement was done with a recently developed instrument, the Functional Assessment of Cancer Therapy-Head & Neck Symptom Index-10 (FHNSI-10). It is a 10 item symptom-focused index specially designed for advanced and/or recurrent/refractory head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published phase III EXTREME study showed that adding Cetuximab (human chimeric monoclonal antibody against EGFR) to platinum and 5-FU significantly prolonged the median OS from 7.4 months to 10.1 months in recurrent and/or metastatic SCCHN. 24 Quality of life (QOL) measurement was done with a recently developed instrument, the Functional Assessment of Cancer Therapy-Head & Neck Symptom Index-10 (FHNSI-10). It is a 10 item symptom-focused index specially designed for advanced and/or recurrent/refractory head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Other cancers A comparison of platin-5-fluorouracil alone versus combination with cetuximab as first-line treatment in recurrent or metastatic squamous cell cancer of the head and neck region showed no significant differences in most HRQOL scores between the two treatment arms, but patients in the cetuximab arm displayed significant improvements in pain, swallowing problems, speech and social eating problems [Rivera et al 2009].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Proof of principle was obtained in a Phase III study of first line cisplatin plus cetuximab, which demonstrated improved overall survival in metastatic head and neck cancer patients [38]. Wirth et al investigated the feasibility of combining panitumumab, carboplatin and two dose levels of paclitaxel with radiation delivered using IMRT as primary treatment in patients with advanced head and neck cancer [39].…”
Section: Newer Targeted Agentsmentioning
confidence: 99%